2007
DOI: 10.1128/jvi.02094-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotavirus Strain on the Murine Model of Biliary Atresia

Abstract: Biliary atresia is a devastating disorder of the newborn in which afflicted infants develop inflammation and fibrosis of the extrahepatic biliary tract, resulting in cirrhosis and end-stage liver disease. Infection with a virus is thought to be a contributing factor in the etiology of biliary atresia. In the murine model of biliary atresia, perinatal exposure to rhesus rotavirus (RRV) results in biliary epithelial cell infection causing bile duct obstruction. The purpose of this study was to determine if tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
96
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 34 publications
(36 reference statements)
9
96
1
Order By: Relevance
“…Although previous studies reported a tropism of RRV to cholangiocytes and the ability of RRV to replicate and lyse cholangiocytes in vitro (8,29), our data show that cholangiocyte infection alone is not sufficient to induce biliary atresia. Instead, it appears that infected cells are secondarily targeted by activated NK cells, which use the Nkg2d receptor to establish contact, injure cholangiocytes, and initiate a break in epithelial integrity.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Although previous studies reported a tropism of RRV to cholangiocytes and the ability of RRV to replicate and lyse cholangiocytes in vitro (8,29), our data show that cholangiocyte infection alone is not sufficient to induce biliary atresia. Instead, it appears that infected cells are secondarily targeted by activated NK cells, which use the Nkg2d receptor to establish contact, injure cholangiocytes, and initiate a break in epithelial integrity.…”
Section: Discussioncontrasting
confidence: 47%
“…Consistent with this function, the number of NK cells in the ducts substantially increased upon RRV challenge in the immediate postnatal period. This response aims at clearing infected cells, as supported by the ability of RRV-primed NK cells to promote lysis of cholangiocytes, one of the main cellular targets of neonatal RRV infection (8,29). In doing so, NK cells disrupt the duct mucosa, produce proinflammatory signals, and promote an extension of the injury that leads to duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that in the murine model of biliary atresia, RRV targeted the biliary epithelial cell (cholangiocyte) for infection (1,31). To determine the basis for cholangiocyte susceptibility to RRV, an in vitro model of RRV infection of the two dominant cell types found within the liver (cholangiocytes and hepatocytes) was established.…”
mentioning
confidence: 99%
“…It was also noted that NSP4 elicits systemic and intestinal antibody responses in gnotobiotic pig and rabbit models (17,21) and induces diarrhea in newborn mice (17,22). Recently, biliary atresia (BA), a fibroinflammatory pediatric liver disease that is the primary indication for liver transplantation in children, has been demonstrated to occur in rotavirus infection (3,23,24). Osteopontin (OPN), a glycoprotein with inflammatory and fibrogenic activity, may play a pathogenic role in BA (25).…”
Section: Discussionmentioning
confidence: 99%